Antioxidant properties of resveratrol: A structure–activity insight - Guelcin, Ilhami (Innovative food science & emerging technologies, 2010)
Resveratrol, a natural product, is known to affect a broad range of intracellular mediators. In the present study, we clarified the antioxidant activity of resveratrol by employing various in vitro antioxidant assays such as DPPH•, ABTS •+, DMPD •+, O 2 •− and H 2O 2 scavenging activities, total antioxidant activity, reducing abilities, and Fe 2+ chelating activities. Resveratrol inhibited 89.1% of the lipid peroxidation of linoleic acid emulsion at 30 µg/mL concentration. On the other hand, BHA, BHT, α-tocopherol, and trolox exhibited inhibitions of 83.3, 82.1, 68.1, and 81.3% against peroxidation of linoleic acid emulsion at the same concentration, respectively. In addition, resveratrol had effective DPPH•, ABTS •+, DMPD •+, O 2 •− and H 2O 2 scavenging activities, reducing power, and Fe 2+ chelating activities. The present study found that resveratrol had effective in vitro antioxidant and radical scavenging activity. It can be used in pharmacological and food industry due to its antioxidant properties. Antioxidants are often added to foods to prevent the radical chain reactions of oxidation and they act by inhibiting the initiation and propagation step leading to the termination of the reaction and delay the oxidation process. At the present time, the most commonly used antioxidants are BHA, BHT, propylgallate and tert-butyl hydroquinone. Besides that BHA and BHT are restricted by legislative rules because of doubts over their toxic and carcinogenic effects. Therefore, there is a growing interest on natural and safer antioxidants in food applications, and a growing trend in consumer preferences for natural antioxidants, all of which has given more impetus to explore natural sources of antioxidants. A variety of foods and beverages of vegetable origin contain several nonflavonoid classes of phenolic compounds synthesized by plants. Among them, resveratrol has been identified as the major active compound of stilbene phytoalexins and is presumed to be beneficial for human health. Resveratrol is naturally occurring in the fruits and leaves of edible plants, peanuts, mulberries, grapes and red wine. Resveratrol is currently in the limelight all over the world due to their beneficial effects on the human body. Resveratrol can be used for minimizing or preventing lipid oxidation in pharmaceutical products, retarding the formation of toxic oxidation products, maintaining nutritional quality and prolonging the shelf life of food products and pharmaceuticals instead of BHA and BHT and other antioxidant compounds because of their safer usage.